2023
DOI: 10.1111/1750-3841.16486
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of physicochemical characteristics, flavor profiles and functional properties in Chinese radishes via spontaneous fermentation after drying

Abstract: Spontaneously dried–fermented radishes have been consumed in China for hundreds of years and are usually fermented for a long time to acquire high quality. In this study, the spontaneously dried–fermented radishes with short‐term manufacturing periods were made from five different varieties of radishes that grew in the same environment. In addition, the physicochemical characteristics (i.e., moisture content, soluble solid, and pH value), flavor profiles (i.e., free amino acids, organic acids, and volatile com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(86 reference statements)
2
2
0
Order By: Relevance
“…Additionally, volatile substances such as sulphide-containing compounds, alcohols, acetic acid, carbonyls and acetals contribute to the overall aroma profile of PR (Li & Liu, 2022). Consistent with the findings of Zheng et al (2023), our study also identified ITCs as the most abundant volatile compounds in both groups of PR. Specifically, Hexane, 1-ITC-, Propane, trans-Raphasatin and Berteroin were identified, contributing to the distinct pungent odour and potential anti-cancer activity of PR (Wei et al, 2021).…”
Section: Effect Of Dvs On Volatile Flavor Substances Of Prsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, volatile substances such as sulphide-containing compounds, alcohols, acetic acid, carbonyls and acetals contribute to the overall aroma profile of PR (Li & Liu, 2022). Consistent with the findings of Zheng et al (2023), our study also identified ITCs as the most abundant volatile compounds in both groups of PR. Specifically, Hexane, 1-ITC-, Propane, trans-Raphasatin and Berteroin were identified, contributing to the distinct pungent odour and potential anti-cancer activity of PR (Wei et al, 2021).…”
Section: Effect Of Dvs On Volatile Flavor Substances Of Prsupporting
confidence: 88%
“…Consistent with the findings of Zheng et al . (2023), our study also identified ITCs as the most abundant volatile compounds in both groups of PR. Specifically, Hexane, 1‐ITC‐, Propane, trans‐Raphasatin and Berteroin were identified, contributing to the distinct pungent odour and potential anti‐cancer activity of PR (Wei et al ., 2021).…”
Section: Resultssupporting
confidence: 63%
“…Texture, especially hardness and chewiness, plays a critical role in consumer acceptance of fermented radishes. This makes certain varieties, such as WW, RR, and GG, more suitable for this type of product ( Zheng et al, 2023 ; Zhou et al, 2023 ). In addition, GG has a higher hardness and chewiness than other radish varieties, with values of 33.71 N and 30.44 mJ, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, pickling and fermentation could improve its taste and enrich its nutritional value. [ 2 ] “Lao Caipu,” a traditional food of China, is made of white radish with coarse salt. It's known as the “competition ginseng” and “gastrointestinal protection God” in folklore.…”
Section: Introductionmentioning
confidence: 99%